Traditional ecological knowledge sustains due to poverty and lack of choices rather than thinking about the environment - Abdullah Abdullah; Shujaul Mulk Khan (BMC, 2023)
Abstract In this debate article, we have tried to discuss Traditional Ecological Knowledge (TEK) and its close link to the available resources and lack of options in the indigenous communities. We came across the article of Hartel et al. where they initiated a discussion on this important but debatable topic of TEK and its merits and demirits for the environment. We believe that this discourse could continue to clarify both sides of the picture. Our research group is working on species facing extinction threats due to extensive utilization, leading to overexploitation of the taxa, which the TEK seldom cares for. We are of the opinion that the marginalized tribal communities living around the globe extensively use some of the species and natural resources for their food, fodder, fiber, shelter, energy, health and other benefits, irrespective of their conservation needs, and many other ecosystem services. They have to sustain their basic live's needs from the resources available for their livelihood. They collect economically important medicinal and other species in large quantities to gain higher earnings, rather than thinking of the issues faced by them. Hence, we believe that the continuity and utilization of TEK are driven by poverty and lack of choices rather than positive environmental values, historically. Nevertheless, those communities sometimes have their local system of protection which sometimes works very well or otherwise with the passage of time and the formation of government-driven regulations in the recent past, TEK itself has lost its real sense especially, related to conservation and management. Therefore, TEK could be linked with existing research-based policies and regulations for long-lasting benefits to the environment and its sustainable future. Such bridging can benifit all the stake hoders-the TEK holders, regulatory bodies, government agencies and many more. This debate can lead to a positive and critical discourse towards the clarification of the conundrum under consideration as well as creation of more questions hyptheses related to TEK.